Brasil, país do futuro: segundo Stefan Zweig e Agostinho da Silva - Siewierski, Henryk (2007)
Stefan Zweig and Agostinho da Silva, each in his own way, witnessed the present and looked towards the future of Brazil wherein they saw a possibility of a better future for the whole world. ln Stefan Zweig's oeuvre Brazil holds an episodic, albeit distinct, position as the tragic conclusion of his life. ln Agostinho da Silva's work Brazil is a privileged subject as well as the experience of a biography closely intertwined with the history of that country. Stefan Zweig's and Agostinho da Silva's views converged in regarding Brazil as an alternative cultural and developmental model in relation to the contemporary Europe, a model which they considered superior in that it was based on humanistic and universally Christian values which had no longer served as the basis for the Old World. There are, however, significant differences. For example, in Stefan Zweig's vision of Brazil the processes of homogenization and unification are highlighted and idealized, whereas Agostinho da Silva emphasizes Brazil's diversity and liberty.